The role of water in the reversibility of thermal denaturation of lysozyme in solid and liquid states - Tuan Phan-Xuan; Ekaterina Bogdanova; Jens Sommertune; Anna Millqvist Fureby; Jonas Fransson; Ann E. Terry; Vitaly Kocherbitov (Biochemistry and Biophysics Reports, 2021)
Although unfolding of protein in the liquid state is relatively well studied, its mechanisms in the solid state, are much less understood. We evaluated the reversibility of thermal unfolding of lysozyme with respect to the water content using a combination of thermodynamic and structural techniques such as differential scanning calorimetry, synchrotron small and wide-angle X-ray scattering (SWAXS) and Raman spectroscopy. Analysis of the endothermic thermal transition obtained by DSC scans showed three distinct unfolding behaviors at different water contents. Using SWAXS and Raman spectroscopy, we investigated reversibility of the unfolding for each hydration regime for various structural levels including overall molecular shape, secondary structure, hydrophobic and hydrogen bonding interactions. In the substantially dehydrated state below 37 wt% of water the unfolding is an irreversible process and can be described by a kinetic approach; above 60 wt% the process is reversible, and the thermodynamic equilibrium approach is applied. In the intermediate range of water contents between 37 wt% and 60 wt%, the system is phase separated and the thermal denaturation involves two processes: melting of protein crystals and unfolding of protein molecules. A phase diagram of thermal unfolding/denaturation in lysozyme - water system was constructed based on the experimental data.